Selection of Turbine Integrated Gas Compressor For Turbine - Ismayilov, Aqil (My University, 2025)
The growing demand for high-efficiency power generation, together with reduced fuel consumption and environmentally sustainable energy systems, focuses attention on improving gas turbine performance through advanced thermodynamic modeling and component integration. Among the most critical elements of any gas turbine are the compressor and turbine, whose aerodynamic and thermal behavior largely determines the overall cycle efficiency, work output, and operational reliability. This thesis concerns the thermodynamic integration of a three-stage axial gas compressor with a single expansion turbine, based on the development of an integrated analytical and computational framework for studying its performance, power balance, and efficiency characteristics under realistic industrial conditions. The compressor in this work is modeled stage by stage, including such details as interstage temperature rise, pressure development, work input, and isentropic versus polytropic efficiency. The turbine model assumes realistic expansion processes and takes into consideration turbine inlet temperature and energy balance in the calculation of work output as well as exhaust temperature and pressure. The model also contains a heat exchanger that recuperates thermal energy from turbine exhaust to preheat compressor fuel before entering the combustion chamber. Given such a configuration, a more realistic simulation can be achieved regarding how waste heat from modern industrial gas turbine systems is utilized to gain higher cycle efficiency. A computational platform with Python, including the full integration model, has been developed. It iterates the compressor and turbine performances over a wide range of operating conditions. The results obtained for the three-stage compressor show high values of cumulative temperature rise and specific work requirements, reflecting its sensitivity to interstage efficiency and pressure ratio distribution. One realizes the importance of distinguishing polytropic from isentropic efficiency, since the former is a direct measure of stage-by-stage compression behavior, while the latter gives an extended thermodynamic comparison. Then, on the turbine side, the model showed that turbine expansion efficiency, turbine inlet temperature, and exhaust pressure are each strong influences on the ability of the turbine to drive both the compressor and deliver useful shaft power. The sensitivity analysis underlines the tradeoffs between compressor work and turbine output that must be made-a balance that essentially defines whether the integrated system can function. In this paper, a comprehensive thermodynamic analysis of compressor–turbine matching has been carried out, pointing out the influence of the choice of pressure ratio, stage efficiency, combustion heating, and exhaust conditions on the performance of an integrated gas turbine. The result of the present work provides valuable insight into the design and optimization of industrial gas turbines, together with a computational framework that is easily extended to more complex multi-stage, multi-spool, or cooled turbine configurations. This thesis finally enhances the understanding of interdependent behavior that exists between compressors and turbines and provides a scientifically grounded approach to predict performance in real-world gas turbine applications.
Keywords: Compressor-Turbine Matching; Thermal Performance; Waste Heat Recovery; Thermodynamic Modeling; Python Simulation; Heat Recovery; Axial Compressor